Promising Treatments for Obsessive-Compulsive Disorder: A Call for Additional Research - M Koran, Lorrin; Aboujaoude, Elias (Current medicinal chemistry, 2018)
Many patients with OCD respond partially or not at all to standard medications and cognitive behavioral therapy approaches, making alternate treatments necessary. We review the preliminary evidence that exists in support of the use of stimulants, high-dose caffeine, opiates, memantine, ondansetron, ketamine, and transcranial magnetic stimulation in some patients with OCD. Although limited by small or modest sample sizes, open-label study designs, and brief follow-up periods, studies suggest that each of these strategies can help some patients who have inadequately responded to first-line treatments. The existing data and the unmet needs of OCD patients justify research attention to further test these treatments' safety and efficacy. Previously untested drugs also deserve attention, especially as recent research has suggested new possible contributors to OCD pathophysiology. Similarly, psychotherapeutic interventions beyond CBT should be investigated, and treatments with preliminary evidence in OCD, including Acceptance Commitment Therapy, Danger Ideation Reduction Therapy, and technology-enabled interventions like computerized CBT and Virtual Reality Exposure Therapy, should be carefully tested.